Studies on Vegetative Propagation in Ficus glomerata L. Moraceae Stem Cuttings - Bhati, Bhagwati P.; Badoni, Arun K. (Indian Forester, 1993)
Stem cuttings of Ficus glomerata were treated with various concentrations of I.B.A. and N.A.A. (0.1,0.2,0.5 and 1.0mgml-1) for 24 hrs by the month of August 1988 and the observations were recorded after 90 days. I.B.A. at 0.5 and 1.0 mgml-1 concentration level enhanced maximum rooting response as well as sprouting percentage. N.A.A. at (0.1 and 0.2 mgml-l) was found suitable for initiation in branch cuttings. 1.0 mgml-1 of I.B.A. and 0.1 mgml-l of N.A.A. are promising concentrations for rooting response and largest root lengths of cuttings.